Soft magnetic composite powder as well as preparation method and application thereof

By forming a composite oxide coating of titanium dioxide and alumina on the surface of the soft magnetic powder, the problem of high magnetic loss of metal soft magnetic materials at high frequencies is solved, and soft magnetic with lower magnetic loss and higher mechanical strength is achieved Compound powder.

CN119407165APending Publication Date: 2025-02-11HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411599304.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing metal soft magnetic materials have high magnetic losses at high frequencies, and insufficient insulation coating effect and mechanical strength, which affects their application in electronic components.

Method used

By mixing the titanium halide and aluminum halide with soft magnetic powder, an electrolyte, alkali liquid mixing and heat treatment process is used to form a composite oxide coating layer coated with titanium dioxide and alumina on the surface of the soft magnetic powder.

Benefits of technology

It realizes soft magnetic composite powder with uniform coating, high mechanical strength, excellent insulation effect and lower magnetic loss at high frequencies, ensuring the low eddy current loss characteristics of the magnetic powder core.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127831750000141
    Figure BDA0005127831750000141
  • Figure BDA0005127831750000151
    Figure BDA0005127831750000151
Patent Text Reader

Abstract

The invention relates to soft magnetic composite powder and a preparation method and application thereof, and the preparation method comprises the following steps: (1) mixing titanium halide, aluminum halide, a solvent and soft magnetic powder to obtain a mixture; (2) electrifying and electrolyzing the mixture, and then mixing the electrolyzed product with alkali liquor to obtain a solid product; and (3) carrying out heat treatment on the solid product to obtain the soft magnetic composite powder. According to the preparation method provided by the invention, the titanium halide and the aluminum halide are taken as raw materials and are mixed with the soft magnetic powder, and a coating structure in which the surface of the soft magnetic powder is coated with the titanium dioxide and the surface of the titanium dioxide is coated with the aluminum trioxide is formed by adopting an electrified electrolysis process, an alkali liquor mixing process and a heat treatment process; the obtained soft magnetic composite powder is good in coating uniformity, high in mechanical strength, excellent in insulation effect and lower in magnetic loss under high frequency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal soft magnetic materials, and in particular to a soft magnetic composite powder and a preparation method and application thereof. Background Art

[0002] Soft magnetic materials are widely used in computer technology, new energy, power electronics, and telecommunication engineering industries. Traditional iron core materials have a low frequency range of application due to high eddy current loss; ferrite materials have good high-frequency loss characteristics, but their saturation magnetization is low and it is difficult to meet the requirements of device miniaturization. As an important soft magnetic material, metal soft magnetic has the advantages of high saturation magnetization, good frequency characteristics, and good heat dissipation coefficient. After mixing with an insulating binder, it can be prepared into a metal soft magnetic powder core with better performance through molding, annealing, impregnation and curing.

[0003] With the development of electronic components in miniaturization, high frequency, high current and energy saving, the development and iteration of metal soft magnetic materials are getting faster and faster, especially the demand for soft magnetic materials with lower loss at high frequency is increasing. Therefore, how to further reduce the loss of materials has become a problem that the industry is paying more attention to and solving.

[0004] At present, the properties and surface treatment of magnetic powder are the key to improving the high-frequency properties of metal soft magnetic materials. In order to improve the resistivity of magnetic powder cores, it is usually chosen to coat the surface of magnetic powder, and the surface properties of the powder are improved by organic, inorganic, and organic-inorganic methods, so that it has an insulating layer with high resistivity and reduces the eddy current loss between particles. Prior art CN102360661A uses phenolic resin to optimize the high-frequency loss of iron silicon soft magnetic powder cores, but due to the increase in hysteresis loss, the effect is not obvious; Prior art CN101089108A ​​uses SiO2, Al2O3, mica powder, etc. to coat magnetic particles to improve the magnetic properties of magnetic powder cores, but because oxide particles are directly added and are in physical contact with soft magnetic particles, there are problems such as uneven coating and low bonding strength, which leads to low mechanical strength of the material, thereby affecting the insulation coating effect.

[0005] Therefore, providing a method for preparing soft magnetic powder with uniform coating, good insulation coating effect and high mechanical strength, so as to obtain soft magnetic powder with lower magnetic loss at high frequency, has become an urgent problem to be solved. Summary of the invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a soft magnetic composite powder and its preparation method and use. The preparation method provided by the present invention uses titanium halide and aluminum halide as raw materials, mixes with soft magnetic powder, and adopts an electric electrolysis process, an alkali solution mixing process and a heat treatment process to form a coating structure in which titanium dioxide is coated on the surface of the soft magnetic powder and aluminum oxide is coated on the surface of the titanium dioxide. The obtained soft magnetic composite powder has good coating uniformity, high mechanical strength, excellent insulation effect and lower magnetic loss at high frequency.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a soft magnetic composite powder, the preparation method comprising the following steps:

[0009] (1) mixing titanium halide, aluminum halide, solvent and soft magnetic powder to obtain a mixture;

[0010] (2) electrolyzing the mixture, and then mixing the electrolyzed product with an alkaline solution to obtain a solid product;

[0011] (3) heat treating the solid product to obtain the soft magnetic composite powder.

[0012] The preparation method provided by the present invention comprises the following steps: titanium halide is firstly hydrolyzed to obtain titanium dioxide and halide ions during a mixing process, and the titanium dioxide is coated on the surface of a soft magnetic powder. The pH value of the mixture after the titanium halide is hydrolyzed is less than 2. Under the acidic condition, the mixture after the hydrolysis is electrolyzed by an electric electrolysis process to ionize all aluminum ions in the aluminum halide. Then, an alkaline solution is added to increase the pH value in the mixture to induce a hydrolysis reaction of the aluminum ions to form a hydroxide precipitate. Subsequently, under a heat treatment process, the aluminum hydroxide precipitate is converted into aluminum trioxide, which is coated on the surface of the titanium dioxide coated on the surface of the soft magnetic powder, thereby obtaining a composite oxide coating layer in which the titanium dioxide surface is coated with aluminum trioxide. The titanium dioxide and aluminum trioxide in the composite oxide coating layer prepared by the above-mentioned specific process are both nano-grade materials.

[0013] The preparation method provided by the present invention uses titanium halide and aluminum halide as raw materials, mixes them with soft magnetic powder, and then adopts the synergistic effect of an electric electrolysis process, an alkali solution mixing process and a heat treatment process to form a coating structure in which titanium dioxide is coated on the surface of the soft magnetic powder and aluminum oxide is coated on the surface of the titanium dioxide. The coating layer with a specific composition and structure is uniformly and tightly coated on the surface of the soft magnetic powder, greatly improving the insulation resistance of the surface of the soft magnetic powder and effectively reducing the magnetic loss of the soft magnetic powder at high frequency. In addition, the coating layer composed of nanomaterials and the high bonding strength between the coating layer and the soft magnetic powder make the obtained soft magnetic composite powder have higher mechanical strength, which can avoid the damage of the coating layer on the surface of the soft magnetic powder in the subsequent preparation process of the magnetic powder core, thereby ensuring the characteristic of low eddy current loss of the magnetic powder.

[0014] Preferably, the titanium halide in step (1) comprises any one of titanium tetrachloride, titanium tetrabromide or titanium tetraiodide, or a combination of at least two thereof.

[0015] Preferably, the aluminum halide in step (1) includes any one of aluminum trichloride, aluminum tribromide or aluminum triiodide, or a combination of at least two of them.

[0016] Preferably, the soft magnetic powder in step (1) comprises any one of sendustine aluminum magnetic powder, iron silicon magnetic powder, iron nickel magnetic powder, iron silicon chromium magnetic powder, iron nickel molybdenum magnetic powder, amorphous magnetic powder or nanocrystalline magnetic powder, or a combination of at least two thereof.

[0017] Preferably, the particle size of the soft magnetic powder in step (1) is 80-1200 mesh, for example, 80 mesh, 100 mesh, 200 mesh, 300 mesh, 400 mesh, 500 mesh, 600 mesh, 700 mesh, 800 mesh, 900 mesh, 1000 mesh, 1100 mesh or 1200 mesh.

[0018] Preferably, the specific process of the mixing in step (1) includes: preparing titanium halide and solvent to form a titanium halide solution, preparing aluminum halide and solvent to form an aluminum halide solution, and then mixing the titanium halide solution, aluminum halide solution and soft magnetic powder to obtain a mixture.

[0019] Preferably, the concentration of the titanium halide solution is 0.5-10 mol / L, such as 0.5 mol / L, 1 mol / L, 2 mol / L, 4 mol / L, 6 mol / L, 8 mol / L or 10 mol / L, etc., preferably 0.5-8 mol / L.

[0020] Preferably, the concentration of the aluminum halide solution is 0.5-15 mol / L, for example, 0.5 mol / L, 1 mol / L, 2 mol / L, 4 mol / L, 6 mol / L, 8 mol / L, 10 mol / L, 12 mol / L, 14 mol / L or 15 mol / L, etc., preferably 0.5-8 mol / L.

[0021] Preferably, the volume ratio of the titanium halide solution to the aluminum halide solution is (2-8):(2-8), for example, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3 or 8:2, etc.

[0022] The present invention further regulates the volume ratio of titanium halide solution and aluminum halide solution of specific concentrations, and can adjust the oxide layers of TiO2 and Al2O3 of different thicknesses, thereby ensuring effective coating of soft magnetic powder and further optimizing the coating effect.

[0023] Preferably, the ratio of the mass of the soft magnetic powder to the total mass of the titanium halide solution and the aluminum halide solution is 1:(1-10), for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10, etc.

[0024] The present invention further regulates the ratio of the mass of the soft magnetic powder to the total volume of the titanium halide solution and the aluminum halide solution, thereby regulating the relative content of the soft magnetic powder and the composite oxide of the coating layer, while ensuring that the soft magnetic composite powder has a higher magnetic permeability, and can also effectively reduce the magnetic loss characteristics of the soft magnetic composite powder.

[0025] Preferably, the current of the electrolysis in step (2) is 1-10A, such as 1A, 2A, 3A, 4A, 5A, 6A, 7A, 8A, 9A or 10A.

[0026] The present invention further regulates the current of the electrolysis, and can adjust the oxide generation rate by controlling the speed of hydrolysis, thereby further optimizing the coating effect of the coating layer of the soft magnetic composite powder, forming a soft magnetic composite powder with both high magnetic permeability and low magnetic loss.

[0027] Preferably, the time for electrolysis in step (2) is 10-300 s, for example, 10 s, 30 s, 50 s, 100 s, 150 s, 200 s, 250 s or 300 s.

[0028] The present invention further regulates the time of electrolysis to ensure that the aluminum ions in the mixture are completely ionized, so that the oxide generation reaction is more complete.

[0029] Preferably, the alkali solution in step (2) comprises any one of aqueous ammonia, sodium hydroxide, sodium bicarbonate or potassium bicarbonate, or a combination of at least two thereof, preferably aqueous ammonia.

[0030] Preferably, the pH value of the mixed solution in step (2) is 2-13, such as 2, 4, 6, 8, 10, 12 or 13, and preferably 2-10.

[0031] The present invention adjusts the pH value of the product by adding alkaline solution to the product after electrolysis to meet the requirement of hydrolyzing aluminum ions to generate aluminum hydroxide precipitates, and further adjusts the specific pH value to ensure complete hydrolysis of aluminum ions.

[0032] Preferably, the mixing time in step (2) is 0.5-20 h, for example 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h or 20 h, etc.

[0033] Preferably, the mixing in step (2) is followed by separation and washing.

[0034] In the present invention, there is no specific limitation on the separation method, including but not limited to filtration, centrifugation or sedimentation, and those skilled in the art can select according to needs.

[0035] In the present invention, there is no specific limitation on the washing method, including but not limited to flushing, ultrasound or vibration, etc., and those skilled in the art can select according to needs.

[0036] In the present invention, there is no specific limitation on the washing solvent, including but not limited to water or ethanol, etc., and those skilled in the art can select it according to needs.

[0037] Preferably, the temperature of the heat treatment in step (3) is 80-1000°C, for example, 80°C, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C, etc., preferably 500-1000°C.

[0038] Preferably, the heat treatment time in step (3) is 0.5-10 h, for example 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.

[0039] In a second aspect, the present invention provides a soft magnetic composite powder, which is prepared by the preparation method described in the first aspect.

[0040] The soft magnetic composite powder provided by the present invention has good insulation effect and lower magnetic loss at high frequency, and it also has excellent mechanical strength, which can avoid the damage to the material structure caused by the pre-pressing process in the subsequent application in the preparation of soft magnetic powder cores, thereby ensuring that the soft magnetic powder in the powder core can still maintain a complete structure and have the characteristics of lower eddy current loss.

[0041] Preferably, the soft magnetic composite powder comprises a soft magnetic powder core and a Ti—Al composite oxide coating layer coated on the surface of the soft magnetic powder.

[0042] Preferably, the Ti—Al composite oxide coating layer comprises TiO 2 and Al 2 O 3 .

[0043] Preferably, the TiO2 is located on the inner side of the coating layer, close to the soft magnetic powder core; the Al2O3 is located on the outer side of the coating layer, away from the soft magnetic powder core.

[0044] Preferably, the Al2O3 is coated on the surface of the TiO2.

[0045] In a third aspect, the present invention provides a soft magnetic powder core, wherein the soft magnetic powder core comprises the soft magnetic composite powder as described in the second aspect.

[0046] The soft magnetic powder core provided by the present invention comprises a specific soft magnetic composite powder, which can effectively improve the magnetic properties of the powder core and show lower magnetic loss under high-frequency conditions.

[0047] In a fourth aspect, the present invention provides a method for preparing the soft magnetic powder core as described in the third aspect, the preparation method comprising the following steps:

[0048] The soft magnetic composite powder as described in the second aspect is mixed with a binder and a release agent, and subjected to pre-pressing and annealing treatment to obtain the soft magnetic powder core.

[0049] The preparation method of the soft magnetic powder core provided by the present invention uses soft magnetic composite powder with specific composition and structure as raw material, mixes it with a binder and a release agent, and prepares a high-performance soft magnetic powder core through pre-pressing and annealing treatment. The soft magnetic composite powder in the obtained soft magnetic powder core still maintains its special structure, thereby effectively reducing the eddy current loss of the soft magnetic powder core at high frequency.

[0050] Preferably, the adhesive is any one of epoxy resin, phenolic resin or polyimide, or a combination of at least two of them.

[0051] Preferably, the release agent comprises barium stearate and / or calcium stearate.

[0052] Preferably, the mass ratio of the soft magnetic composite powder to the binder is 1:(0.005-0.05), for example, 1:0.005, 1:0.01, 1:0.015, 1:0.02, 1:0.025, 1:0.03, 1:0.035, 1:0.04, 1:0.045 or 1:0.05, etc.

[0053] Preferably, the mass ratio of the soft magnetic composite powder to the release agent is 1:(0.001-0.02), for example, 1:0.001, 1:0.002, 1:0.004, 1:0.006, 1:0.008, 1:0.01, 1:0.012, 1:0.014, 1:0.016, 1:0.018 or 1:0.02, etc.

[0054] Preferably, the pre-pressing pressure is 500-2000 MPa, for example, 500 MPa, 600 MPa, 800 MPa, 1000 MPa, 1200 MPa, 1400 MPa, 1600 MPa, 1800 MPa or 2000 MPa.

[0055] Preferably, the atmosphere of the annealing treatment includes a nitrogen atmosphere and / or an inert atmosphere.

[0056] Preferably, the gas used in the inert atmosphere includes any one of helium, neon or argon.

[0057] Preferably, the annealing temperature is 500-900°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C.

[0058] Preferably, the annealing treatment time is 0.5-5 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h.

[0059] Compared with the prior art, the present invention has at least the following beneficial effects:

[0060] (1) The preparation method provided by the present invention uses titanium halide and aluminum halide as raw materials, mixes them with soft magnetic powder, and then adopts the synergistic effect of electric electrolysis process, alkali solution mixing process and heat treatment process to form a coating structure in which titanium dioxide is coated on the surface of soft magnetic powder and aluminum oxide is coated on the surface of titanium dioxide. The coating layer with specific composition and structure is evenly and tightly coated on the surface of soft magnetic powder, which greatly improves the insulation resistance of the surface of soft magnetic powder and effectively reduces the lower magnetic loss of soft magnetic powder at high frequency. In addition, the coating layer composed of nano material and the high bonding strength between the coating layer and the soft magnetic powder make the obtained soft magnetic composite powder have higher mechanical strength, which can avoid the damage of the coating layer on the surface of soft magnetic powder in the subsequent preparation process of magnetic powder core, thereby ensuring the characteristic of low eddy current loss of magnetic powder.

[0061] (2) The soft magnetic composite powder provided by the present invention has good insulation effect and lower magnetic loss at high frequency, and it also has excellent mechanical strength, which can avoid the damage to the material structure caused by the pre-pressing process in the subsequent application in the preparation of soft magnetic powder cores, thereby ensuring that the soft magnetic powder in the powder core can still maintain a complete structure and have the characteristics of lower eddy current loss.

[0062] (3) The soft magnetic powder core provided by the present invention includes a specific soft magnetic composite powder, which can effectively improve the magnetic properties of the powder core and exhibit lower magnetic loss under high frequency conditions.

[0063] (4) The preparation method of the soft magnetic powder core provided by the present invention uses soft magnetic composite powder of specific composition and structure as raw material, mixes it with a binder and a release agent, and prepares a high-performance soft magnetic powder core through pre-pressing and annealing treatment. The soft magnetic composite powder in the obtained soft magnetic powder core still maintains its special structure, thereby effectively reducing the eddy current loss of the soft magnetic powder core at high frequency. DETAILED DESCRIPTION

[0064] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0065] Example 1

[0066] This embodiment provides a method for preparing a soft magnetic composite powder, comprising the following steps:

[0067] (1) A titanium tetrachloride solution with a concentration of 0.5 mol / L and an aluminum trichloride solution with a volume ratio of 2:8 were prepared with deionized water as a solvent, and 100 g of the mixed solution was added to 100 g of 500-mesh iron-nickel magnetic powder and the mixture was mixed to obtain a mixture.

[0068] (2) Electrodes were added to the mixture obtained in step (1) and a current of 1 A was passed through for electrolysis for 10 seconds. Then, aqueous ammonia was added dropwise to adjust the pH value of the electrolytic product to 3. After reacting for 0.5 hours, the solid-liquid separation was performed and the product was washed with deionized water to obtain a solid product.

[0069] (3) The solid product obtained in step (2) is heat treated at 600°C for 2 hours to obtain a soft magnetic composite powder, wherein the soft magnetic composite powder is composed of an inner core of iron-nickel magnetic powder, a TiO2 coating layer coating the iron-nickel magnetic powder, and an Al2O3 coating layer coated on the TiO2 coating layer.

[0070] This embodiment also provides a method for preparing a soft magnetic powder core, which specifically includes the following steps:

[0071] The soft magnetic composite powder prepared above was mixed with epoxy resin and barium stearate, wherein the mass ratio of the soft magnetic composite powder to the epoxy resin was 1:0.005, and the mass ratio of the soft magnetic composite powder to the barium stearate was 1:0.001. The mixed product was pre-pressed at 1000 MPa, and then annealed at 600°C for 0.5 h in a nitrogen atmosphere to obtain a soft magnetic powder core.

[0072] Example 2

[0073] This embodiment provides a method for preparing a soft magnetic composite powder, comprising the following steps:

[0074] (1) A titanium tetrabromide solution with a concentration of 1.5 mol / L and an aluminum tribromide solution with a concentration of 3 mol / L were prepared with deionized water as a solvent, and the titanium tetrabromide solution and the aluminum tribromide solution were mixed in a volume ratio of 4:6. 200 g of the mixed solution was taken, and 100 g of 500-mesh iron-nickel magnetic powder was added and continued to mix to obtain a mixture.

[0075] (2) Electrodes were added to the mixture obtained in step (1) and a current of 3 A was passed through for electrolysis for 30 seconds. Then, aqueous ammonia was added dropwise to adjust the pH value of the electrolytic product to 5. After reacting for 2 hours, the solid-liquid separation was performed and the product was washed with deionized water to obtain a solid product.

[0076] (3) The solid product obtained in step (2) is heat treated at 900°C for 2 hours to obtain a soft magnetic composite powder, wherein the soft magnetic composite powder is composed of an inner core of iron-nickel magnetic powder, a TiO2 coating layer coating the surface of the iron-nickel magnetic powder, and an Al2O3 coating layer coated on the TiO2 coating layer.

[0077] This embodiment also provides a method for preparing a soft magnetic powder core, which specifically includes the following steps:

[0078] The soft magnetic composite powder prepared above was mixed with phenolic resin and calcium stearate, wherein the mass ratio of the soft magnetic composite powder to the phenolic resin was 1:0.008, and the mass ratio of the soft magnetic composite powder to calcium stearate was 1:0.003. The mixed product was pre-pressed at 1500MPa, and then annealed at 700°C for 1h in a nitrogen atmosphere to obtain a soft magnetic powder core.

[0079] Example 3

[0080] This embodiment provides a method for preparing a soft magnetic composite powder, comprising the following steps:

[0081] (1) A 2.5 mol / L titanium tetraiodide solution and a 3 mol / L aluminum triiodide solution were prepared with deionized water as a solvent, and the titanium tetraiodide solution and the aluminum triiodide solution were mixed in a volume ratio of 6:4. 300 g of the mixed solution was taken, and 100 g of 500-mesh sendust magnetic powder was added and continued to mix to obtain a mixture.

[0082] (2) Electrodes were added to the mixture obtained in step (1) and a current of 3 A was passed through for electrolysis for 50 seconds. Then, aqueous ammonia was added dropwise to adjust the pH value of the electrolytic product to 7. After reacting for 5 hours, the solid-liquid separation was performed and the product was washed with deionized water to obtain a solid product.

[0083] (3) The solid product obtained in step (2) is heat treated at 800°C for 4 hours to obtain a soft magnetic composite powder, wherein the soft magnetic composite powder is composed of a core of sendust magnetic powder, a TiO2 coating layer coating the surface of the sendust magnetic powder, and an Al2O3 coating layer coated on the TiO2 coating layer.

[0084] This embodiment also provides a method for preparing a soft magnetic powder core, which specifically includes the following steps:

[0085] The soft magnetic composite powder prepared above is mixed with epoxy resin and barium stearate, wherein the mass ratio of the soft magnetic composite powder to the phenolic resin is 1:0.01, and the mass ratio of the soft magnetic composite powder to the barium stearate is 1:0.005. The mixed product is pre-pressed at 1500MPa, and then annealed at 800°C for 2h in a nitrogen atmosphere to obtain a soft magnetic powder core.

[0086] Example 4

[0087] This embodiment provides a method for preparing a soft magnetic composite powder, comprising the following steps:

[0088] (1) A titanium tetrachloride solution with a concentration of 5.5 mol / L and an aluminum trichloride solution with a concentration of 8 mol / L were prepared with deionized water as a solvent, and the titanium tetrachloride solution and the aluminum trichloride solution were mixed in a volume ratio of 8:2. 400 g of the mixed solution was taken, and 100 g of 500-mesh sendust magnetic powder was added and continued to mix to obtain a mixture.

[0089] (2) Electrodes were added to the mixture obtained in step (1) and a current of 5 A was passed through the mixture for 80 seconds for electrolysis. Then, sodium hydroxide was added dropwise to adjust the pH value of the electrolytic product to 9. After reacting for 10 hours, the solid-liquid separation was performed and the product was washed with deionized water to obtain a solid product.

[0090] (3) The solid product obtained in step (2) is heat treated at 500°C for 8 hours to obtain a soft magnetic composite powder, wherein the soft magnetic composite powder is composed of a core of sendust magnetic powder, a TiO2 coating layer coating the surface of the sendust magnetic powder, and an Al2O3 layer coated on the TiO2 coating layer.

[0091] This embodiment also provides a method for preparing a soft magnetic powder core, which specifically includes the following steps:

[0092] The soft magnetic composite powder prepared above was mixed with epoxy resin and calcium stearate, wherein the mass ratio of the soft magnetic composite powder to the phenolic resin was 1:0.012, and the mass ratio of the soft magnetic composite powder to the calcium stearate was 1:0.008. The mixed product was pre-pressed at 1800 MPa, and then annealed at 900°C for 3 hours in a nitrogen atmosphere to obtain a soft magnetic powder core.

[0093] Example 5

[0094] The difference between this embodiment and embodiment 1 is that in the method for preparing the soft magnetic composite powder provided in this embodiment, the volume ratio of the titanium tetrachloride solution to the aluminum trichloride solution is 1:9. The rest of the contents are the same as those in embodiment 1.

[0095] Example 6

[0096] The difference between this embodiment and embodiment 1 is that in the method for preparing the soft magnetic composite powder provided in this embodiment, the volume ratio of the titanium tetrachloride solution to the aluminum trichloride solution is 9:1. The rest of the contents are the same as those in embodiment 1.

[0097] Example 7

[0098] The difference between this embodiment and embodiment 1 is that in the method for preparing the soft magnetic composite powder provided in this embodiment, 100 g of 500-mesh iron-nickel magnetic powder is added to 20 g of the mixed solution. The rest of the contents are the same as those in embodiment 1.

[0099] Example 8

[0100] The difference between this embodiment and embodiment 1 is that in the method for preparing the soft magnetic composite powder provided in this embodiment, 1200 g of the mixed solution is added with 100 g of 500-mesh iron-nickel magnetic powder. The rest of the contents are the same as those in embodiment 1.

[0101] Example 9

[0102] The difference between this embodiment and embodiment 1 is that in the method for preparing the soft magnetic composite powder provided in this embodiment, electrodes are added to the mixture obtained in step (1) and a current of 0.5 A is passed through for electrolysis. The rest of the contents are the same as those in embodiment 1.

[0103] Example 10

[0104] The difference between this embodiment and embodiment 1 is that in the method for preparing the soft magnetic composite powder provided in this embodiment, electrodes are added to the mixture obtained in step (1) and a current of 11A is passed through for electrolysis. The rest of the contents are the same as those in embodiment 1.

[0105] Comparative Example 1

[0106] The difference between this comparative example and Example 1 is that the preparation method of the soft magnetic composite powder provided in this comparative example comprises the following steps: taking 100g of 500-mesh iron-nickel magnetic powder, adding 100g of 0.2wt% phosphoric acid for passivation, drying, adding titanium oxide and aluminum oxide in a molar ratio of 1:2 for ball milling and mixing, wherein the mass ratio of the iron-nickel magnetic powder to the mass ratio of titanium oxide and aluminum oxide is 1:0.01, and obtaining a soft magnetic composite powder, wherein the composite powder comprises iron-nickel magnetic powder and a composite oxide of TiO2-Al2O3 coated on its surface. The rest of the contents are the same as Example 1.

[0107] Comparative Example 2

[0108] The difference between this comparative example and Example 3 is that the preparation method of the soft magnetic composite powder provided in this comparative example comprises the following steps: taking 100g of 500-mesh sendust magnetic powder, adding 300gmL of 0.2wt% phosphoric acid for passivation, adding titanium oxide and aluminum oxide in a molar ratio of 3:2 after drying, and ball milling and mixing, wherein the mass ratio of the sendust magnetic powder to the mass ratio of titanium oxide and aluminum oxide is 1:0.02, and obtaining a soft magnetic composite powder, wherein the composite powder comprises sendust magnetic powder and a composite oxide of TiO2-Al2O3 coated on its surface. The rest of the contents are the same as Example 3.

[0109] Comparative Example 3

[0110] The difference between this comparative example and Example 1 is that in the preparation method provided in this comparative example, the addition of ammonia water is omitted, and the electrolyzed product is directly subjected to heat treatment. The rest of the contents are the same as Example 1.

[0111] Comparative Example 4

[0112] The difference between this comparative example and Example 1 is that in the preparation method provided in this comparative example, the electrolysis process is omitted, and the mixture obtained in step (1) is directly mixed with ammonia water until the pH value of the product is 3. The rest of the contents are the same as Example 1.

[0113] Comparative Example 5

[0114] The difference between this comparative example and Example 1 is that in the preparation method provided in this comparative example, step (1) and step (2) of Example 1 are replaced by the following process: first, a prepared aluminum chloride solution with a concentration of 0.5 mol / L is mixed with 100 g of 500-mesh iron-nickel magnetic powder to obtain a mixture, an electrode is added to the mixture, a 1A current is passed through the mixture for electrolysis for 30 seconds, and then ammonia water is added dropwise to adjust the pH value of the electrolytic product to 3, and after reacting for 0.5 hours, a prepared titanium tetrachloride solution with a concentration of 0.5 mol / L is then added to the reactant, the solid-liquid separation is performed, and the product is washed with deionized water to obtain a solid product. The rest of the contents are the same as Example 1.

[0115] The soft magnetic powder cores prepared in the above examples and comparative examples were tested for magnetic permeability, loss Pcv (unit power loss) (100kHz, 100mT), and loss Pcv (unit power loss) (500kHz, 50mT). The results are shown in Table 1 below. Wherein:

[0116] (1) Magnetic permeability test:

[0117] A copper wire with a diameter of 0.4 mm was uniformly wound around the soft magnetic powder cores prepared in the above embodiment and comparative example for 30 turns, and the magnetic permeability was tested under the conditions of 100 kHz, 1 V, and 25° C.

[0118] (2) Loss Pcv (100kHz, 100mT) (500kHz, 50mT) test:

[0119] A copper wire with a diameter of 0.4 mm was uniformly wound around the soft magnetic powder cores prepared in the embodiment and the comparative example with 30×5 turns, and the loss Pcv was tested under the conditions of 100 kHz, 100 mT, 25°C and 500 kHz, 50 mT, 25°C.

[0120] Table 1

[0121]

[0122]

[0123] The test results show that:

[0124] (1) It can be seen from Examples 1 to 4 that the preparation method provided by the present invention uses titanium halide and aluminum halide as raw materials, mixes them with soft magnetic powder, and then adopts an electric electrolysis process, an alkali solution mixing process and a heat treatment process to form a composite oxide coating layer composed of inner titanium dioxide and outer aluminum oxide on the surface of the soft magnetic powder, thereby forming a soft magnetic composite powder with uniform coating, high mechanical strength, good insulation effect and lower magnetic loss at high frequency, and further makes the formed soft magnetic powder core have suitable magnetic permeability and lower magnetic loss at high frequency.

[0125] (2) It can be seen from Example 1 and Examples 5 and 6 that the present invention can obtain better TiO2 and Al2O3 coating layers by further regulating the volume ratio of the titanium halide solution and the aluminum halide solution of specific concentrations. If the volume ratio is too large or too small, that is, the amount of titanium halide solution added is small or the amount of aluminum halide solution added is small, the magnetic loss characteristics of the soft magnetic powder core cannot be effectively reduced, and the magnetic permeability of the powder core is reduced.

[0126] (3) It can be seen from Example 1 and Examples 7 and 8 that the present invention further regulates the ratio of the mass of the soft magnetic powder to the total volume of the titanium halide solution and the aluminum halide solution, thereby regulating the relative content of the soft magnetic powder and the composite oxide of the coating layer, so as to achieve a good coating and insulation effect on the magnetic powder. If the ratio of the two is too small, although the non-magnetic phase in the magnetic powder core decreases and the magnetic permeability increases, the decrease in the content of titanium halide and aluminum halide will result in an inability to fully form an insulating layer, thereby increasing the magnetic loss of the formed magnetic powder core; if the ratio of the two is too large, the insulating layer will be thicker and the hysteresis loss will be too large, affecting the loss of the magnetic powder core.

[0127] (4) It can be seen from Example 1 and Examples 9 and 10 that the present invention can further regulate the current of electrolysis and can regulate the electrolysis process. If the current is too small, the electrolysis is insufficient, and the content of metal oxide formed on the surface of the obtained soft magnetic composite powder decreases. Although the magnetic permeability of the magnetic powder core is increased, the magnetic loss of the magnetic powder core is significantly increased. If the current is too large, although the reaction can be sufficient, it will affect the coating effect of the coating layer in the soft magnetic composite powder, and the magnetic loss characteristics cannot be further improved.

[0128] (5) By comparing Example 1 with Comparative Example 1, and Example 3 with Comparative Example 2, it can be seen that if iron-nickel magnetic powder and sendust magnetic powder are directly mixed with titanium oxide and aluminum oxide respectively in the present invention, the magnetic permeability of the obtained soft magnetic powder core decreases, and the unit power loss of the powder core at high frequency increases significantly.

[0129] (6) By comparing Example 1 with Comparative Example 3, it can be seen that if the addition of ammonia water is omitted in the present invention, the reaction cannot proceed, and the magnetic permeability of the obtained magnetic powder core is low and the magnetic loss at high frequency is high.

[0130] (7) By comparing Example 1 with Comparative Example 4, it can be seen that if the electrolysis process is omitted in the present invention, the reaction cannot proceed, and the soft magnetic powder in the obtained soft magnetic composite powder cannot be effectively coated, thereby causing the performance of the formed soft magnetic powder core to deteriorate.

[0131] (8) By comparing Example 1 with Comparative Example 5, it can be seen that in the present invention, if titanium halide is added after the aluminum halide and soft magnetic powder are subjected to the electric electrolysis process and the alkaline solution mixing process, the TiO2 and Al2O3 composite oxide coating layer cannot be formed, thereby affecting the improvement of the performance of the formed soft magnetic powder core.

[0132] In summary, the preparation method provided by the present invention uses titanium halide and aluminum halide as raw materials, mixes them with soft magnetic powder, and then adopts the synergistic effect of an electric electrolysis process, an alkali solution mixing process and a heat treatment process to form a coating structure in which titanium dioxide is coated on the surface of the soft magnetic powder and aluminum oxide is coated on the surface of the titanium dioxide. The coating layer with a specific composition and structure is uniformly and tightly coated on the surface of the soft magnetic powder, which greatly improves the insulation resistance of the surface of the soft magnetic powder and effectively reduces the lower magnetic loss of the soft magnetic powder at high frequencies. In addition, the coating layer composed of nanomaterials and the high bonding strength between the coating layer and the soft magnetic powder make the obtained soft magnetic composite powder have higher mechanical strength, which can avoid damage to the coating layer on the surface of the soft magnetic powder in the subsequent preparation process of the magnetic powder core, thereby ensuring the characteristic of lower eddy current loss of the magnetic powder.

[0133] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a soft magnetic composite powder, characterized in that: The preparation method comprises the following steps: (1) mixing titanium halide, aluminum halide, solvent and soft magnetic powder to obtain a mixture; (2) electrolyzing the mixture, and then mixing the electrolyzed product with an alkaline solution to obtain a solid product; (3) heat treating the solid product to obtain the soft magnetic composite powder.

2. The preparation method according to claim 1, characterized in that: The titanium halide in step (1) includes any one of titanium tetrachloride, titanium tetrabromide or titanium tetraiodide, or a combination of at least two thereof; Preferably, the aluminum halide in step (1) comprises any one of aluminum trichloride, aluminum tribromide or aluminum triiodide, or a combination of at least two thereof; Preferably, the soft magnetic powder in step (1) comprises any one of sendustine-aluminum magnetic powder, iron-silicon magnetic powder, iron-nickel magnetic powder, iron-silicon-chromium magnetic powder, iron-nickel-molybdenum magnetic powder, amorphous magnetic powder or nanocrystalline magnetic powder, or a combination of at least two thereof; Preferably, the particle size of the soft magnetic powder in step (1) is 80-1200 mesh.

3. The preparation method according to claim 1 or 2, characterized in that: The specific process of the mixing in step (1) comprises: preparing a titanium halide and a solvent to form a titanium halide solution, preparing an aluminum halide and a solvent to form an aluminum halide solution, and then mixing the titanium halide solution, the aluminum halide solution and the soft magnetic powder to obtain a mixture; Preferably, the concentration of the titanium halide solution is 0.5-10 mol / L, preferably 0.5-8 mol / L; Preferably, the concentration of the aluminum halide solution is 0.5-15 mol / L, preferably 0.5-8 mol / L; Preferably, the volume ratio of the titanium halide solution to the aluminum halide solution is (2-8):(2-8); Preferably, the ratio of the mass of the soft magnetic powder to the total mass of the titanium halide solution and the aluminum halide solution is 1:(1-10).

4. The preparation method according to any one of claims 1 to 3, characterized in that The current of the electrolysis in step (2) is 1-10A; Preferably, the electrolysis time in step (2) is 10-300s; Preferably, the alkali solution in step (2) comprises any one of aqueous ammonia, sodium hydroxide, sodium bicarbonate or potassium bicarbonate, or a combination of at least two thereof, preferably aqueous ammonia; Preferably, the pH value of the mixed solution in step (2) is 2-13, preferably 2-10; Preferably, the mixing time in step (2) is 0.5-20h; Preferably, the mixing in step (2) is followed by separation and washing.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the heat treatment in step (3) is 80-1000° C., preferably 500-1000° C.; Preferably, the heat treatment time in step (3) is 0.5-10 h.

6. A soft magnetic composite powder, characterized in that: The soft magnetic composite powder is prepared by the preparation method according to any one of claims 1 to 5.

7. The soft magnetic composite powder according to claim 6, characterized in that: The soft magnetic composite powder comprises a soft magnetic powder core and a Ti-Al composite oxide coating layer coated on the surface of the soft magnetic powder; Preferably, the Ti-Al composite oxide coating layer comprises TiO2 and Al2O3; Preferably, the TiO2 is located on the inner side of the coating layer, close to the soft magnetic powder core; the Al2O3 is located on the outer side of the coating layer, away from the soft magnetic powder core; Preferably, the Al2O3 is coated on the surface of the TiO2.

8. A soft magnetic powder core, characterized in that: The soft magnetic powder core comprises the soft magnetic composite powder according to claim 6 or 7.

9. A method for preparing a soft magnetic powder core according to claim 8, characterized in that: The preparation method comprises the following steps: The soft magnetic composite powder according to claim 6 or 7 is mixed with a binder and a release agent, and subjected to pre-pressing and annealing treatment to obtain the soft magnetic powder core.

10. The preparation method according to claim 9, characterized in that: The binder is any one of epoxy resin, phenolic resin or polyimide or a combination of at least two thereof; Preferably, the release agent comprises barium stearate and / or calcium stearate; Preferably, the mass ratio of the soft magnetic composite powder to the binder is 1:(0.005-0.05); Preferably, the mass ratio of the soft magnetic composite powder to the release agent is 1:(0.001-0.02); Preferably, the pre-pressing pressure is 500-2000MPa; Preferably, the atmosphere of the annealing treatment includes a nitrogen atmosphere and / or an inert atmosphere; Preferably, the gas used in the inert atmosphere includes any one of helium, neon or argon; Preferably, the annealing temperature is 500-900°C; Preferably, the annealing treatment time is 0.5-5h.

Citation Information

Patent Citations

  • Inorganic insulating adhesive for soft magentic metal powder core andits prepn process

    CN101089108A

  • Iron-silicon alloy soft magnetic material with permeability mu of 75 and manufacturing method thereof

    CN102360661A